Violência psicológica no casal: gênero, cultura da honra e regulação emocional - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
It is a qualitative and quantitative research aimed at investigating the occurrence of psychological violence in the intimate partner, in its bidirectional character, taking into account the influence of gender stereotypes, honor culture and emotional regulation in the experiences of abusive relationships; using as theoretical reference the assumptions of Cultural-historical Psychology developed by Vygotsky. The research methodology proposes the construction of data through instruments available in an online platform, containing closed questions about abusive relationship, honor culture and emotions control, socio-demographic questionnaire and an open question about love relationship, consisting of an experience report. Qualitative data from the open question were evaluated based on the Discourse Analysis. On the quantitative data, inferential analyzes of Correlation through Pearson r were performed to study the relationship between the various phenomena, in order to understand the interaction that they present. It was intended to identify which characteristics are related to the presence of abusive relationships and how these are constituted in the participants' discourse. In general, discourses revealed several forms of psychological violence in the couple, such as threatening, cursing, humiliation, being betrayed, being accused of treason, vigilance, indifference and criticism; and were permeated by sexist ideology. Quantitative analyzes did not find differences between the situation of suffering and practicing violence, according to gender and revealed that violence is bidirectional in 61% of the cases. Suffering psychological violence correlated with the practice of all other forms of abuse. Physical violence suffered was the highest indicator of psychological abuse. Worries about honor and emotional suppression moderated the relationship with psychological violence. Honor concerns had the opposite inverse effect, that is, the greater the level of adherence to norms typical of the culture of honor, the greater the likelihood that the subject would respond with psychological abuse to the experiences of psychological violence suffered. When considering emotional suppression, there was a reduction in individuals' propensity to counteract psychological abuse behavior.
Psychological violence in the intimate partner: gender, honor culture and emotion regulation
Keywords: Violência psicológica; Violência por parceiro íntimo; Gênero; Cultura da honra; Regulação emocional; Psicologia histórico-cultural; Psychological violence; Intimate partner violence; Gender; Honor culture; Emotion Regulation; Cultural-historical psychology; CIÊNCIAS HUMANAS: PSICOLOGIA